A divulgação científica da produção de professores em formação continuada do mestrado em educação em ciências - polo Parintins/AM - Carvalho, Mary Tânia dos Santos (2012)
It was investigated on the repercussions of the Scientific Popularization of the Scientific Knowledge systematized by 15 (fifteen) Teachers of the Pole Parintins, that went by a process of Continuous Formation in the Course of Master's degree in Education in Sciences, of the Program of Powders - Graduation in Education Teaching of Sciences in the Amazonian, of the University of the State of Amazon. It was had as parameter the participation of the subjects investigated in Scientific Events in the following scales: place (Seminar: The courses Investigative in Education in Sciences in the Pole / Parintins), Regional (XX EPENN and I DRY), National (VIII ENPEC accomplished in Campinas / SP). theoretical Considerations regarding the Scientific Popularization (DC) they were articulate to penetrate in an a more detailed vision of the presence of the science and technology in our society, as well as the Scientific Culture in the Dynamics of the Production of the Science, also defined as "dynamics of the scientific culture". In the methodological procedure the qualitative approach was prioritized through the bibliographical research and technical of the participant observation research of field exploratory, combined ace, questionnaires, interviews semi - structured centered in the Focal Group. The accomplishment of the interviews semi - structured with the Teachers in Continuous Formation (PFC) they happened in two ways, in the first it was the delivery of the interview form printed, and on Monday I send of the interview form for email, participant observation happened during the meetings of the Nucleus of Studies and Research in Scientific Education of Parintins - NEPECIP. The results showed the reflection as one of the important points of the Program of Master's degree in Education in Sciences in the Amazonian, leaving evident that the Scientific Production is in a cumulative process built by the actions of all the enterprising of the process: teachers / researchers / advisors, master degree / researchers / teachers.